Bone-Anchored Hearing Aid vs. Reconstruction of the External Auditory Canal in Children and Adolescents with Congenital Aural Atresia: A Comparison Study of Outcomes - Don, Debra M.; Farnoosh, Soroush; Mitsinikos, Tania; Maceri, Dennis (Frontiers in Pediatrics, 2014)
Objectives/Hypothesis: Congenital aural atresia is a rare condition in children affecting 1 in 10,000 to 20,000 children a year. Surgery is required to restore hearing to facilitate normal development. The objective of this study was to compare outcomes in hearing, complications and quality of life of surgical reconstruction of the external auditory canal (EACR) and bone-anchored hearing aid (BAHA) in a pediatric population with congenital aural atresia. Study Design: Subjects were children who had a diagnosis of congenital aural atresia or stenosis and who received either BAHA or EACR. Methods: The medical records of 68 children were reviewed for operative complications and audiometric results. A quality of life questionnaire was prospectively administered to a subset of subjects. Results: Pre-operatively, air conduction threshold were not significantly different between groups at 500, 1000, 2000 and 4000 Hz (p>0.05). Post-operatively, the BAHA group (44.3 ± 14.3 and 44.5 ± 11.3) demonstrated a significantly larger hearing gain than the EACR group (20.0 ± 18.9 and 15.3 ± 19.9) in both the short and long-term periods (p<0.001). Overall the incidence of complications and need for revision surgery were comparable between groups (p>0.05). Quality of life assessment revealed no statistical significance between the two groups (p>0.05) Conclusion: Although the quality of life and incidence of surgical complications between the two interventions was not significantly different, BAHA implantation appears to provide a better, more reliable audiologic outcome than EACR.